2021
DOI: 10.3390/w13192720
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of Soil Moisture on Canopy Transpiration Using a Modified Jarvis-Stewart Model

Abstract: In dryland regions, soil moisture is an important limiting factor for canopy transpiration (T). Thus, clarifying the impact of soil moisture on T is critical for comprehensive forest—water management and sustainable development. In this study, T, meteorological factors (reference evapotranspiration, ETref), soil moisture (relative soil water content, RSWC), and leaf area index (LAI) in a Larix principis-rupprechtii plantation of Liupan Mountains in the dryland region of Northwest China were simultaneously moni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…This study evaluated the interannual variability of transpiration of western juniper saplings and its correlation with several environmental variables of interest (i.e., SM, ST, Pr, SR, AT, RH, and VPD). Plant transpiration rates are affected by water availability and weather variables [10,[36][37][38]. Study results showed that juniper sapling transpiration in both the Mays-East and Mays-West sites followed a similar pattern, conforming to the effects of seasonal precipitation on soil moisture availability in cool-climate rangeland ecosystems of semiarid central Oregon, USA.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…This study evaluated the interannual variability of transpiration of western juniper saplings and its correlation with several environmental variables of interest (i.e., SM, ST, Pr, SR, AT, RH, and VPD). Plant transpiration rates are affected by water availability and weather variables [10,[36][37][38]. Study results showed that juniper sapling transpiration in both the Mays-East and Mays-West sites followed a similar pattern, conforming to the effects of seasonal precipitation on soil moisture availability in cool-climate rangeland ecosystems of semiarid central Oregon, USA.…”
Section: Discussionmentioning
confidence: 78%
“…Many environmental variables, including soil moisture, soil temperature, air temperature, solar radiation, relative humidity, vapor pressure deficit, and precipitation, help explain the process of plant transpiration [8]. Different studies have indicated that soil moisture plays an important role in transpiration [9][10][11]. Other studies [8,12] have reported that tree transpiration was closely related to changes in solar radiation and vapor pressure Hydrology 2023, 10, 232 2 of 14 deficit.…”
Section: Introductionmentioning
confidence: 99%
“…Transpiration and related water-use strategies are fundamental to understanding the physiological processes of plantations and play a vital role in their survival and growth, especially in semiarid and arid regions, where water availability is greatly affected by the increased frequency and intensity of droughts [8,9]. However, previous studies have shown that the effects of excessive water loss caused by transpiration and its environmental driving factors differ significantly, resulting in different growth performances among different functional types [10][11][12]. Therefore, it is imperative to understand the transpiration processes and dynamics of planted tree and shrub species and how these processes change from their normal functions.…”
Section: Introductionmentioning
confidence: 99%
“…Jarvis [36] proposed a serial empirical formula to express the relationship between leaf stomatal conductance and environmental factors; this formula has been widely used and modified [37,38]. Transpiration and sap flow have also been linked directly with environmental factors by analogy with the stomatal conductance formulation [39][40][41][42]. In this study, we used sap flux density to investigate the environmental controls using Equation (3).…”
Section: Discussionmentioning
confidence: 99%